Talking About Antismoking Campaigns: What Do Smokers Talk About, and How Does Talk Influence Campaign Effectiveness?. Issue 1 (2nd January 2016) - Brennan, Emily; Durkin, Sarah J.; Wakefield, Melanie A.; Kashima, Yoshihisa
Abstract : Campaign-stimulated conversations have been shown to increase the effectiveness of antismoking campaigns. In order to explore why such effects occur, in the current study we coded the content of naturally occurring conversations. We also examined whether the short-term effects of talking, and of different types of talk, on quitting intentions were mediated through intrapersonal message responses. Using the Natural Exposure SM methodology, we exposed 411 smokers to 1 of 6 antismoking advertisements while they were watching television at home. Responses to the advertisement—conversation participation and content, emotional responses, personalized perceived effectiveness, and changes in intentions to quit—were measured within 3 days of exposure. Conversations were coded for appraisal of the advertisement (favorable, neutral, or unfavorable) and the presence of quitting talk and emotion talk. Mediation analyses indicated that the positive effects of talking on intention change were mediated through personalized perceived effectiveness and that the positive effects were driven by conversations that contained a favorable appraisal and/or quitting talk. Conversely, conversations that contained an unfavorable appraisal of the advertisement were negatively associated with campaign effectiveness. These findings highlight the importance of measuring interpersonal communication when evaluating campaigns and the need for further research to identify the message characteristics that predict when smokers talk and when they talk only in desirable ways.